Effectiveness of Peribulbar (Extracone) Anesthesia in Comparison with Combined Retrobulbar and Facial Nerve Block for Anterior Ocular Surgery - , Ifthkhar Ahmed, Abdul Hameed Khokhar, Raiz Baloch (Pakistan Journal of Ophthalmology, 2007)
Purpose: To compare the effectiveness of combined retro bulbar and facial nerve block, alone with that of peribulbar block, for anterior ocular surgery. Material and Method: One hundred and fifty patients were randomly divided into two groups. Group 1 received retro bulbar block combined with facial never block. Group 2 received peribulbar block. Anesthetic agent used was a mixture of equal volumes of 2% Xylocaine and 0.5% bupivacaine. Twenty minutes after the block the effectiveness was assessed on the basis of eyelid movements, ocular movement and intraocular pressure. Results: Sixty nine patients (92%) in group I and 67 (92%) patients in-group II had complete blockade of lid movements. One (1.33%) patient in group I and two (2.66%) patients in-group II had almost normal eyelid movements and required a supplementary block. Three (4%) patients in group I and two (2.66%) in group II had almost normal eyeball movements. One patient (1.3%) in group I developed a hard eye due to retrobulbar hemorrhage. Sixty-two (82.66%) patients in group I and forty-two (56%) in group II had intraocular pressure (IOP) less than15 mm Hg. Conclusion: No significant difference was found in overall effectiveness of anesthesia between the two groups.